2022
DOI: 10.3389/fimmu.2022.970321
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of immune parameters, miRNA-mRNA interaction, and immune genes expression in the liver of rainbow trout following infectious hematopoietic necrosis virus infection

Abstract: Rainbow trout (Oncorhynchus mykiss) is an important economical cold-water fish worldwide. However, infection with infectious hematopoietic necrosis virus (IHNV) has severely restricted the development of aquaculture and caused huge economic losses. Currently, little is known about the immune defense mechanisms of rainbow trout against IHNV. In this study, we detected the changes of immune parameters over different post-infection periods (6-, 12-, 24-, 48-, 72-, 96-, 120-, and 144 hours post-infection (hpi)), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Rainbow trout ( Oncorhynchus mykiss ), belonging to the Salmonidae family, is native to North America and Russia's Pacific coast, and it is widely farmed as a cold-water fish in the global aquaculture industry ( 2 ). Intensive farming conditions have contributed to economic growth while also leading to complex aquatic environments that make rainbow trout susceptible to pathogens ( 3 ). Infectious hematopoietic necrosis virus (IHNV), which belongs to the genus Novirhabdovirus of the family Rhabdoviridae, is highly pathogenic and widely transmissible, causing not only high mortality in rainbow trout but also brings huge economic losses to the global aquaculture industry ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainbow trout ( Oncorhynchus mykiss ), belonging to the Salmonidae family, is native to North America and Russia's Pacific coast, and it is widely farmed as a cold-water fish in the global aquaculture industry ( 2 ). Intensive farming conditions have contributed to economic growth while also leading to complex aquatic environments that make rainbow trout susceptible to pathogens ( 3 ). Infectious hematopoietic necrosis virus (IHNV), which belongs to the genus Novirhabdovirus of the family Rhabdoviridae, is highly pathogenic and widely transmissible, causing not only high mortality in rainbow trout but also brings huge economic losses to the global aquaculture industry ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rainbow trout (Oncorhynchus mykiss), belonging to the Salmonidae family, is native to North America and Russia's Pacific coast, and it is widely farmed as a cold-water fish in the global aquaculture industry (2). Intensive farming conditions have contributed to economic growth while also leading to complex aquatic environments that make rainbow trout susceptible to pathogens (3). Infectious studies also showed that CHMM, consisting of 12 herbs, enhanced T-SOD activity and LZM content in European eel (14).…”
Section: Introductionmentioning
confidence: 99%